Phosphorus Response and Toxicity in Acacia spp. - Dixit, R. K.; Thomas, M. B.; Farooqui, U. M.; Patra, A. K.; Spurway, M. L. (Indian Forester, 1999)
Three species of Acacia were grown using a range of P rates in a peat/sand (1:1) media. Seedlings were grown in 1 litre pots in a greenhouse. Severe P toxicity occurred in A. baileyana and A. cardiophylla when P rates supplied from 5-6 month, Osmocote 0-18-0 fertilizer exceeded 20g P/m3/month. Toxicity was indicated by severe stunting and often iron chlorosis of the tip growth. The third species was A. pravissima which was tolerant of P levels approximately double (and even higher) those tolerated by the former species. All three species showed increases in the growth parameters measured of stem diameter, height and foliar dry matter when the P application was increased from nil to 10g P/m3/month.